Analysis of the use of environmentally friendly corrosion inhibitors for mild steel in a carbon dioxide saturated chloride solution via experimental design. Issue 2 (21st September 2018) - Vieira Casanova Monteiro, Mariana; Pessu, Frederick; Barker, Richard; Antônio da Cunha Ponciano Gomes, José; Neville, Anne
Abstract : In the oil and gas industry, carbon dioxide (CO2 ) gas dissolved in produced fluids can cause both general and localized corrosion of carbon steel pipelines due to the speciation of carbonic acid. To mitigate corrosion, the injection of inhibitors into the production fluid is one of the most commonly used methods. However, recent changes in regulations has resulted in a requirement for the development of new corrosion inhibitors that conform to European regulations. This paper presents a full two‐level factorial experimental design approach to study individual effects of environmentally friendly classed inhibitor components (phosphate ester, imidazoline, and quaternary amine derivatives) as combined inhibitors and their interactive effects on carbon steel corrosion processes in CO2 ‐saturated 3.5 wt.% NaCl brine. Through the application of in situ electrochemical monitoring, post‐test interferometry, and scanning electron microscopy (SEM) it was possible to determine the influence of each component within the blends and their effect on both general and localized corrosion. Based on 24 h experiments, the phosphate ester derivative reduced general corrosion rate in all blends; imidazoline derivatives reduced the uniform corrosion rate only when it was at the high level in the blend; and the quaternary amine derivative promoted pitting on the surface. Abstract : Eight blends prepared based on a full two‐level factorial experimental design, using three eco friendly components, have been evaluated as corrosion inhibitors for mild steel at 60 °C in a CO2 ‐saturated brine. The results showed that is possible to determine each component influence within the blends and optimize formulation in determinated experimental conditions, from statistical analysis.